Bioelectrical impedance phase angle and the mortality in critically ill children - Yang, Jiongxian; Zhang, Jie; Liu, Jun; Liu, Gang; Qian, Suyun (Frontiers in Nutrition, 2024)
Background: Phase Angle (PhA) is a variable obtained from Bioelectrical Impedance Analysis (BIA). It is highly sensitive and specific and is commonly used in clinical nutrition assessment. Recently, PhA has shown promise in predicting clinical outcomes, especially as a new indicator of mortality, but its use in pediatric research is limited. This study aims to investigate the association between PhA measured at admission using BIA and PICU length of stay (LOS) and 60-day mortality in critically ill children and adolescents.Methods: A consecutive series of pediatric patients in the PICU underwent BIA measurements within 72 hours of admission. All patients met the inclusion and exclusion criteria. Patient demographics, anthropometric measurements, Pediatric Index of Mortality 2 Score (PIM-2), and laboratory exams were recorded. Kaplan-Meier (K-M) survival curves were constructed based on the critical PhA value to assess differences in survival status within the 60-day window. Multivariate cox regression model was employed to illustrate the relationship between PhA and 60-day mortality rates. The Youden's Index method was used to identify the critical cut-off value for PhA in relation to mortality rates. ROC curves provided the area under the curve (AUC) and a 95% confidence interval (CI).Results: A total of 205 pediatric patients (118 boys) were included, with a mean age of 9.2 years (±6.0). Survival curves indicated a cutoff value of 3.1°, with higher survival in patients with PhA ≥3.1° compared to those with PhA <3.1° (F=10.51, P < 0.0001). The area under the ROC curve was 0.70, with a sensitivity of 0.65 and specificity of 0.72. Total hospital LOS was longer in the PhA <3.1° group compared to the PhA ≥3.1° group (P=0.000). The PhA <3.1° group had a longer PICU LOS (adjusted for age and sex, HR 1.871, P=0.000, Log-rank test, P=0.000). PhA and PIM-2 were two independently significant correlated variables (P<0.05) for the 60-day mortality rate in this study.Low PhA in patients is associated with longer PICU LOS and an increased risk of PICU patient mortality. PhA not only serves as an indicator for monitoring pediatric nutrition but also as a prognostic indicator for PICU patients.